APPLICATION OF EDUCATIONAL DATA ANALYSIS METHODS IN THE EVALUATION OF LESSON SCENARIOS IN THE MOSCOW ELECTRONIC SCHOOL - Barannikov, Kirill; Lesin, Sergey; Vachkova, Svetlana; Suleymanov, Ruslan; Kupriyanov, Roman (Revista Inclusiones, 2020)
The article discusses the implementation of educational data mining methodology, including traditional Data Mining methods (classification, clustering, rating analysis, etc.), to identify patterns in the assessment of lesson scenarios in the Moscow Electronic School by experts. The authors describe the educational data mining methodology as an approach to designing organizational and managerial decisions.